TANTANGAN PENGUATAN DIPLOMASI PUBLIK INDONESIA: STUDI KASUS ANALISIS RENCANA STRATEGIS DIREKTORAT INFORMASI DAN DIPLOMASI PUBLIK TAHUN 2025–2029 - Khurin Istiqomah; Siti Habibatus Salma; Adelia Rezaki Putri; Setyo Pratiwi, Tiffany (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
The Directorate General of Information and Public Diplomacy has established a vision of "Enhancing Indonesia's Positive Image in Supporting Diplomatic Resilience Towards a Golden Indonesia 2045." In realizing this vision, the Directorate General of Information and Public Diplomacy carries out a mission that focuses on strengthening public diplomacy, optimizing strategic communication, promoting Indonesia's soft power diplomatic assets, and strengthening the role of the Indonesian diaspora in supporting national development and improving Indonesia's position on the global stage. This paper will review the Directorate General of Information and Public Diplomacy's 2025–2029 strategic planning document. The targets listed in the 2025–2029 strategic planning document are essentially still in the implementation stage so their achievement cannot yet be assessed comprehensively. However, this paper will explore the challenges of program implementation in strengthening public diplomacy and strategic communication, promoting Indonesia's soft power diplomatic assets, and managing and strengthening the role of the Indonesian diaspora. From the findings, the author found that Indonesia's Soft Power Diplomacy strategy tends to be passive, becoming a challenge in Indonesian public diplomacy, especially in achieving the set targets. Overall, the performance targets set out in the document are highly relevant to the Golden Indonesia 2045 vision, as it seeks to build Indonesia's international reputation as a capital for long-term development. Unfortunately, human resource capacity development and technology utilization remain inadequate.